Advanced Microchannel Fabrication Technologies for Biomedical Devices - Sarma U.; Chandra P.; Joshi S.N. (My University, 2025)
In recent times, microchannel and its fabrication have found immense recognition in biomedical applications. It is because, the microchannels provide devices that are economical and portable. They can be widely used in miniaturized biomedical devices with lab-on-a-chip concept such as electrochemical sensors, microfluidic devices, circuit patterning and microreactors. Thus, keeping in view the importance of the microchannels, this chapter reviews several advanced fabrication technologies of microchannels such as lithography, microwire moulding, imprinting, direct laser micromachining and laser-induced plasma-assisted ablation, each with many advantages and disadvantages. A brief study on the operation principle of each of these fabrication processes, its process parameters, process capabilities and its recent advancements is conveyed. It has been found that laser has certain advantages over the other fabrication technologies. It has proved to be most time saving and precise. As such, discussion on the laser fabrication technology of microchannel is presented with more emphasis on it. Additionally, some of the experimental results of microchannel formation and its thermal bonding to get a closed microchannel have also been presented. This chapter signifies the diverse applications of the microchannels as well. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.